Changing perceptions of weight in Great Britain: comparison of two population surveys. (10th July 2008) - Johnson, F; Cooke, L; Croker, H; Wardle, Jane
Abstract : Objectives To examine changes in public perceptions of overweight in Great Britain over an eight year period. Design Comparison of data on self perceived weight from population surveys in 1999 and 2007. Setting Household surveys of two representative samples in Great Britain. Participants 853 men and 944 women in 1999, and 847 men and 989 women in 2007. Main outcome measures Participants were asked to report their weight and height and classify their body size on a scale from "very underweight" to "obese." Results Self reported weights increased dramatically over time, but the weight at which people perceived themselves to be overweight also rose significantly. In 1999, 81% of overweight participants correctly identified themselves as overweight compared with 75% in 2007, demonstrating a decrease in sensitivity in the self diagnosis of overweight. Conclusions Despite media and health campaigns aiming to raise awareness of healthy weight, increasing numbers of overweight people fail to recognise that their weight is a cause for concern. This makes it less likely that they will see calls for weight control as personally relevant.